Joint attention behaviours in people with profound intellectual and multiple disabilities: the influence of the context. Issue 6 (2nd October 2015) - Neerinckx, Heleen; Maes, Bea
Abstract : Background: In spite of the profound cognitive and physical problems, people with profound intellectual and multiple disabilities (PIMD) are able to develop joint attention behaviours (JAB) and benefit from positive interactions. Aims: To investigate which context factors influence the JAB of people with PIMD. Method: Based on video recordings of 45 participants, JAB and context factors were analysed. Results: An unstructured interaction situation produced the most responses of a person with PIMD, whereas a structured interaction situation produced the most initiatives. Furthermore, the familiarity of the partner and the familiarity of objects used in the interaction had no influence on the JAB. The sensitivity of the interaction partner was positively related to the presence of JAB. Conclusions: Interaction partners of people with PIMD should be aware of both the ability of people with PIMD to use JAB and the influence of different context factors on these JAB.